Approaches to health policy in bogotá, d.c. (2002)
Health policies in Bogotá, D.C. are influenced by a context and several factors which define their purposes and their practical reach: the conceptual approach to the health-disease problem, focused on the factors which determine health, the international context of globalization, the dominant political project which has been included in Bogota's Development Plan, and the city's and its population's health problems. The main health policies of Bogotá, D.C. are described from this perspective.